BUSINESS STRATEGY TO FACING DECLINING SALES OF PT. NISSAN MOTOR INDONESIA - Dwi Prakoso, Wahyu
Indonesia is the fourth largest population in the world with total population about 265 million. In 2020, Indonesia's population is projected will reach 271 million people. The advantage of the large population owned by Indonesia has a positive impact on automotive sales. It is estimated that significant growth for automotive occurs in the segment of passenger vehicle (PV), estimated at growth until 2020 reaches 6.8%. But in the last three years, PT. Nissan Motor Indonesia is facing declining in sales volume. For 2015 Nissan succeed to sold 46,684 units, but in 2018, was facing small volume of sold only 17,318 units, then only have 1.5% market share in Indonesia. So to improve this condition, the researcher conducted a thorough analysis of the decline in sales of Nissan in order get the right solution. In this research, the Framework is divided into three main steps, starting from the input, then the process, and finally the outputs. In the input explain the business issue, in the process is explaining about business exploration, and finally on the outputs explaining business solution. In the business exploration reseaecher use internal & external analysis, and find the main rootcause use fish bone analysis. For business solution find the best alternative use SWOT analysis and TOWS matrix analysis for generate alternative, then choosing the best alternative will use the Analythic Hierarchy Process (AHP) process. As a result, the main factor that affect to the declining sales of nissan are turn over new model is too long plus and expensive spare part for maintain nissan cars. Then for improve this condition, Nissan could be launch new model that build from alliance plant & improve total delivery cost and integrating part supply with alliance plant.